A study of government hospital libraries in Metro Manila - Montefalcon, Juanito S.J (1994)
This study was undertaken in order to present a comprehensive information about the present state of nine government hospital libraries in Metro Manila. The study was conducted during the first semester of school year 1993-1994. In gathering the desired data, a constructed questionnaire, interview of librarians, on-the-spot observation and documentary analysis were employed.